Race in the Reading: A Study of Problematic Uses of Race and Ethnicity in a Prominent Pediatrics Textbook. (23rd September 2022) - Li, Alice; Deyrup, Andrea T.; Graves, Joseph L.; Ross, Lainie Friedman
Abstract : Purpose: Aspects of medical education and clinical practice continue to reflect the antiquated notion that race is a biologically valid distinction among individuals rather than a social construct. The authors analyzed the use of race and ethnicity in a popular pediatrics textbook to determine if these concepts were being used consistently and correctly. Method: In May 2021, using the search function on the American Academy of Pediatrics (AAP) eBooks platform, the authors searched for 29 race- or ethnicity-related terms (e.g., African, Asian, Black, race) in the AAP Textbook of Pediatric Care, 2nd Edition, which was published in 2016. One researcher extracted direct quotes containing at least one of these search terms. Three researchers independently coded each quote as problematic or nonproblematic with respect to the use of the search terms, excluding examples in which the terms were used in irrelevant contexts (e.g., black box warning). The researchers then identified themes based on the quotes that used race and ethnicity problematically. Results: The search produced 2, 167 total results across the search terms, 806 of which were relevant to race or ethnicity and were analyzed. Problematic quotes: (1) used race or ethnicity as a surrogate for social variables, (2) conflated terminology (e.g., conflated socially defined race with genetic ancestry), (3) overgeneralized or made claims based on limited data, (4) lacked clinical relevance, (5) lacked inclusivity, (6) promoted racial stereotypes, or (7) made contradicting claims about race. Conclusions: The use of race and ethnicity in the AAP Textbook of Pediatric Care, 2nd Edition was not always appropriate, as demonstrated by examples that reified race as a biological fact and thereby promoted structural racism. Critical evaluation of the use of race and ethnicity in all current medical textbooks and future revisions is warranted.